Validation of Urinary Glycosaminoglycans in Iranian patients with Mucopolysaccharidase type I: The effect of urine sedimentation characteristics - ABDI, Mohammad; HAKHAMANESHI, Mohammad Said; ALAEI, Mohammad Reza; AZADI, Namam-Ali; VAKILI, Rahim; ZAMANFAR, Daniel; TAGHIKHANI*, Mohammad; KHATAMI*, Shohreh (Iranian Journal of Child Neurology, 2014)
How to Cite This Article:Abdi M, Khatami Sh, Hakhamaneshi MS, Alaei MR, Azadi NA, Zamanfar D, Taghikhani M.Validation of Urinary Glycosaminiglycans in Iranian Patients with Mucopolysaccharidose Type I: The Effect of Urine Sedimentation Characteristics. Iran J Child Neurol. 2014; 8(4):39-45. Abstract Objective The first line-screening test for mucopolysaccharidosis is based on measurement of urinary glycosaminoglycans. The most reliable test for measurement of urine glycosaminoglycans is the 1,9-dimethyleneblue colorimetric assay. Biological markers are affected by ethnical factors, for this reason, the World Health Organization recommends that the diagnostic test characteristics should be used to determine results for different populations. This study determines the diagnostic value of 1,9-dimethyleneblue tests for diagnosis of mucopolysaccharidosis type I patients in Iran. Materials & Methods In addition to routine urine analysis, the qualitative and quantitative measurements of urine glucosaminoglycans were performed with the Berry spot test and 1,9-dimethyleneblue assay. Diagnostic values of the tests were determined using the ROC curve. Results Urine total glycosaminoglycans were significantly higher in male subjects than in female subjects. Glycosaminoglycan concentration was markedly decreased in specimens with elevated white blood cell and epithelial cells count. Using a cut-off level of 10.37 mg/g creatinine, sensitivity, and specificity were 100% and 97.22%, respectively, for a 1,9-dimethyleneblue colorimetric assay. Conclusion Urine glycosaminoglycans concentration significantly differs in our studied population. In addition to determine diagnostic validity of the 1,9-dimethyleneblue test, our results demonstrate the usefulness of measuring glycosaminoglycans for early screening of mucopolysaccharidosis type I Iran. References Jackson RL, Busch SJ, Cardin AD. Glycosaminoglycans: molecular properties, protein interactions, and role in physiological processes. Physiological reviews. 1991 Apr;71(2):481-539. Ghaderi S. The biochemistry base of mucopolysaccharidoses and approach to. Genetics in the 3rd millennium. [Educational]. 2006;4(1):711-22. Mizumoto S, Ikegawa S, Sugahara K. Human genetic disorders caused by mutations in genes encoding biosynthetic enzymes for sulfated glycosaminoglycans. The Journal of biological chemistry. 2013 Apr 19;288(16):10953-61. Salbach J, Rachner TD, Rauner M, Hempel U, Anderegg U, Franz S, et al. Regenerative potential of glycosaminoglycans for skin and bone. Journal of molecular medicine (Berlin, Germany). 2012 Jun;90(6):625-35. Coppa GV, Catassi C, Gabrielli O, Giorgi PL, Dall’Amico R, Naia S, et al. Clinical application of a new simple method for the identification of mucopolysaccharidoses. Helvetica paediatrica acta. 1987 Jun;42(5-6):419-23. Fuller M, Meikle PJ, Hopwood JJ. Glycosaminoglycan degradation fragments in mucopolysaccharidosis I. Glycobiology. 2004 May;14(5):443-50. Fuller M, Rozaklis T, Ramsay SL, Hopwood JJ, Meikle PJ. Disease-specific markers for the mucopolysaccharidoses. Pediatric research. 2004 Nov;56(5):733-8. Blau N, Duran M, Gibson K. Laboratory Guide to the Methods in Biochemical Genetics. First edition ed: Springer-Verlag Berlin Heidelberg; 2008. pp287-324. Dorfman A, Matalon R. The Hurler and Hunter syndromes. The American journal of medicine. 1969 Nov;47(5):691-707. Fratantoni JC, Hall CW, Neufeld EF. Hurler and Hunter syndromes: mutual correction of the defect in cultured fibroblasts. Science (New York, NY. 1968 Nov 1;162(3853):570-2. Fratantoni JC, Hall CW, Neufeld EF. The defect in Hurler and Hunter syndromes. II. Deficiency of specific factors involved in mucopolysaccharide degradation. Proceedings of the National Academy of Sciences of the United States of America. 1969 Sep;64(1):360-6. Fratantoni JC, Neufeld EF, Uhlendorf BW, Jacobson CB. Intrauterine diagnosis of the hurler and hunter syndromes. The New England journal of medicine. 1969 Mar 27;280(13):686-8. Chamoles NA, Blanco MB, Gaggioli D, Casentini C. Hurler-like phenotype: enzymatic diagnosis in dried blood spots on filter paper. Clinical chemistry. 2001 Dec;47(12):2098-102. Nor A, Zabedah MY, Norsiah MD, Ngu LH, Suhaila AR. Separation of sulfated urinary glycosaminoglycans by high-resolution electrophoresis for isotyping of mucopolysaccharidoses in Malaysia. The Malaysian journal of pathology. 2010 Jun;32(1):35-42. De Muro P, Faedda R, Formato M, Re F, Satta A, Cherchi GM, et al. Urinary glycosaminoglycans in patients with systemic lupus erythematosus. Clinical and experimental rheumatology. 2001 Mar-Apr;19(2):125-30. Berry HK, Spinanger J. A paper spot test useful in study of Hurler’s syndrome. The Journal of laboratory and clinical medicine. 1960 Jan;55:136-8. Pennock CA, White F, Murphy D, Charles RG, Kerr H. Excess glycosaminoglycan excretion in infancy and childhood. Acta paediatrica Scandinavica. 1973 Sep;62(5):481-91. Berman ER, Vered J, Bach G. A reliable spot test for mucopolysaccharidoses. Clinical chemistry. 1971 Sep;17(9):886-90. Pennock CA. A review and selection of simple laboratory methods used for the study of glycosaminoglycan excretion and the diagnosis of the mucopolysaccharidoses. Journal of clinical pathology. 1976 Feb;29(2):111-23. Chan RW, Szeto CC. Advances in the clinical laboratory assessment of urinary sediment. Clinica chimica acta; international journal of clinical chemistry. 2004 Feb;340(1-2):67-78. Fogazzi GB, Garigali G. The clinical art and science of urine microscopy. Curr Opin Nephrol Hypertens. 2003 Nov;12(6):625-32. Berry HK. Screening for mucopolysaccharide disorders with the Berry spot test. Clinical biochemistry. 1987 Oct;20(5):365-71. de Jong JG, Hasselman JJ, van Landeghem AA, Vader HL, Wevers RA. The spot test is not a reliable screening procedure for mucopolysaccharidoses. Clinical chemistry. 1991 Apr;37(4):572-5. Mabe P, Valiente A, Soto V, Cornejo V, Raimann E. Evaluation of reliability for urine mucopolysaccharidosis screening by dimethylmethylene blue and Berry spot tests. Clinica chimica acta; international journal of clinical chemistry. 2004 Jul;345(1-2):135-40. Mahalingam K, Janani S, Priya S, Elango EM, Sundari RM. Diagnosis of mucopolysaccharidoses: how to avoid false positives and false negatives. Indian J Pediatr. 2004 Jan;71(1):29-32. de Jong JG, Wevers RA, Laarakkers C, Poorthuis BJ. Dimethyl methylene blue-based spectrophotometry of glycosaminoglycans in untreated urine: a rapid screening procedure for mucopolysaccharidoses. Clinical chemistry. 1989 Jul;35(7):1472-7. Panin G, Naia S, Dall’Amico R, Chiandetti L, Zachello F, Catassi C, et al. Simple spectrophotometric quantification of urinary excretion of glycosaminoglycan sulfates. Clinical chemistry. 1986 Nov;32(11):2073-6. Byers S, Rozaklis T, Brumfield LK, Ranieri E, Hopwood JJ. Glycosaminoglycan accumulation and excretion in the mucopolysaccharidoses: characterization and basis of a diagnostic test for MPS. Molecular genetics and metabolism. 1998 Dec;65(4):282-90. Carson NA, Neill DW. Metabolic abnormalities detected in a survey of mentally backward individuals in Northern Ireland. Archives of disease in childhood. 1962 Oct;37:505-13. Huang KC, Sukegawa K, Orii T. Screening test for urinary glycosaminoglycans and differentiation of various mucopolysaccharidoses. Clinica chimica acta; international journal of clinical chemistry. 1985 Sep 30;151(2):147-56. Chih-Kuang C, Shuan-Pei L, Shyue-Jye L, Tuen-Jen W. MPS screening methods, the Berry spot and acid turbidity tests, cause a high incidence of false-negative results in sanfilippo and morquio syndromes. Journal of clinical laboratory analysis. 2002;16(5):253-8. Gallegos-Arreola MP, Machorro-Lazo MV, Flores-Martinez SE, Zuniga-Gonzalez GM, Figuera LE, Gonzalez-Noriega A, et al. Urinary glycosaminoglycan excretion in healthy subjects and in patients with mucopolysaccharidoses. Archives of medical research. 2000 Sep-Oct;31(5):505-10. Piraud M, Maire I, Mathieu M. Pitfalls of screening for mucopolysaccharidoses by the dimethylmethylene blue test. Clinical chemistry. 1993 Jan;39(1):163-4. Whitley CB, Spielmann RC, Herro G, Teragawa SS. Urinary glycosaminoglycan excretion quantified by an automated semimicro method in specimens conveniently transported from around the globe. Molecular genetics and metabolism. 2002 Jan;75(1):56-64.